The Influence of Argument Quality, Trustworthy Sources, Kindness, on Purchase Intention on TikTok Shop Through Consumer Welfare - Michael Gunawan Hasli; Unik Dwi Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyse the effect of argument quality, trusted sources, and kindness on consumer purchase intention at TikTok Shop, with consumer well-being as a mediating variable. In today's digital era, TikTok Shop as an e-commerce platform is increasingly popular and has become the main means for consumers to make purchases. This research adopts a quantitative approach using a survey method to collect data from 242 respondents who are active users of TikTok Shop. This research is quantitative research using the Lisrel Structural Equation Model (SEM) method. The results showed that trusted sources have an indirect effect on purchase intention, namely through the quality of the argument and also consumer well-being. These findings provide important insights for marketers and sellers at TikTok Shop to understand what influences purchasing decisions. This research is expected to contribute to the development of more effective marketing strategies on social media-based e-commerce platforms.